Inclusive Physical Education and Health (PJOK) Learning Planning Strategy for Slow Learners at Elementary School - Dedi Septiawan; Erick Burhaein (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study is based on the importance of implementing inclusive education in Physical Education, Sports, and Health (PJOK) learning for students with special needs at Tahfidzul Quran Ad Diin Elementary School. The absence of special assistant teachers and the integration of students with special needs in regular classes require appropriate learning planning strategies. This study aims to analyze inclusive PJOK learning planning strategies for students with special needs, especially slow learners. This study uses a qualitative descriptive approach. The population consisted of 87 students in grades IV to VI in the 2025/2026 academic year, with six students selected through purposive sampling. Data collection was conducted through observation, interviews, and documentation. The results showed that learning planning strategies were implemented through four main dimensions: adaptive curriculum, in-depth assessment, modification of learning tools and media, and adaptive learning strategies. The adaptive curriculum is designed so that the objectives and materials are tailored to individual needs. In-depth assessments are conducted at the beginning of the school year as a basis for determining learning objectives and materials. Tools and media are made interactive and game-based. The learning strategy uses an individualized approach, additional learning time, and positive reinforcement to create a supportive environment. With the right planning strategy, it can contribute significantly to improving the motivation, learning effectiveness, and motor development of slow learners.